Examining the relationship between commuting time, academic achievement, and mental health in rural China: a cross-sectional analysis - Hongyu Guan; Jing Xue; Yunyun Zhang; Fang Chang; Wenting Liu (BMC Public Health)
Abstract Background Rearranging school layouts in rural areas has been one of the most important changes to basic education in China since the early 2000s. The layout adjustment has increased the service radius of rural primary schools and increased the distance for students to go to school. While numerous studies have revealed that reducing commuting time would improve positive emotions, limited attention has been given to examining the relationship between commuting time, academic performance, and mental health in China. Methods Using survey data from 12,394 students in 249 rural primary schools in 18 counties, this study examines the association of commuting time on academic performance and mental health among rural students in China. Instrumental variable (IV) estimation techniques are utilized to address potential endogeneity issues and provide robust estimates of the relationships under investigation. Academic performance was measured using the Trends in International Mathematics and Science Study (TIMSS) test, and mental health status was measured using the Mental Health Test (MHT). Results .Lengthy commutes are negatively associated with students’ academic performance and mental health. Each additional hour of commuting time is associated with a 0.148 SD decrease in academic performance and a 3.039 increase in mental health test scores for students, indicating a higher risk of mental health problems. Heterogeneity analysis revealed that the effect of commuting time is more pronounced for female students, senior students, students with migrant parents, and students whose parents have lower education levels. Mechanism analysis demonstrates that sleep duration and after-school outdoor activities mediate the relationship between commuting time, academic achievement, and mental health. Conclusion This study contributes new evidence regarding the association between commuting time, academic performance, and mental health among rural students in China. The findings offer valuable insights for education policymakers in optimizing school location and layout strategies to support students’ academic success and mental well-being. Trial registration Permission was received from local Boards of Education in each region and the principals of all schools. The principles of the Declaration of Helsinki were followed throughout. Oral informed consent was obtained from at least one parent for all child participants. Ethical committee approval for this study were obtained from Sun Yat-Sen University (Registration number: 2013MEKY018) and Stanford University (Registration number: 24847). The trial registration number is ISRCTN03252665 (registered at 25/09/2012).